Penggunaan Media ROTAR Untuk Meningkatkan Hasil Belajar Siswa Kelas IV SD 1 Payaman Kudus - Munia Ningsih; Sumarwiyah Sumarwiyah; Deka Setiawan (Peneliti.net, 2020)
This study aims to describe the increase in sttudent learning outcomes in the realm of knowledge and skills in fourth grade students at SD 1 Payaman through the use of ROTAR media. The research method used was the action reasearch method which was carried out in two cycles of each cycle held wiith two meettings with research participants held with 29 students. Data collection techniques using interview, observation, collection, and test techniques. Data analysis using qualitative analysis and quantitative analysis. The results showed in cycle 1 the realm of student knowledge in social studies load obtained a classical percentage of 89.65% and indonesian content of 93.10%. The results of students skills also increased, the firt cycle containing social studies. Getting a percentage of 68.96% increased in the second cycle with a percentage of 89.65%. on the indonesian load cycle I obtained a percentage of 65.51% increasing in cycle II with a classical percentage of 89.65%. Based on te results of the reseach cycle I and Cycle II through the use of ROTAR media can improve student learning outcomes in grade IV SD 1 Payaman Kudus.